Assessment of agronomic practices among natural rubber farmers in Sintang District, West Kalimantan, Indonesia - SUPRIYANTO SUPRIYANTO; AGUS RULIYANSYAH; NUR ARIFIN; MUHAMMAD PRAMULYA; HENNY SULISTYOWATI (Smujo International, 2025)
Abstract. Supriyanto, Ruliyansyah A, Arifin N, Pramulya M, Sulistyowati H. 2025. Assessment of agronomic practices among natural rubber farmers in Sintang District, West Kalimantan, Indonesia. Asian J Agric 9: 754-765. Smallholder rubber farmers play a crucial role in maintaining the sustainability of the rubber sector in Indonesia; however, their productivity and management practices remain suboptimal. This study assessed the agronomic practices of 470 smallholder rubber farmers in Sintang District, West Kalimantan, Indonesia, using a descriptive-quantitative approach. Data were collected through structured interviews and analyzed using descriptive statistics and Pearson correlation to examine relationships among human resource capacity, socio-economic conditions, and agronomic performance. The results indicate that the majority of farmers are in the productive age group, have low to moderate education, and rely on rubber farming as their primary livelihood. However, farmers tend to prioritize routine operational tasks, such as tapping and latex collection, while key agronomic practices that require more technical knowledge and capital—such as fertilization, the use of certified planting materials, and pest and disease control—remain under-implemented. Correlations indicate that education and access to extension services are positively correlated with the adoption of better agronomic practices, including the use of certified seeds, recommended plant spacing, and proper fertilization. Social roles and group participation also show significant relationships with collective agronomic behavior. These findings highlight the importance of strengthening farmer capacity and institutional support to promote productive and sustainable rubber cultivation among smallholder farmers in Sintang District, West Kalimantan, Indonesia.